2015
DOI: 10.5296/ijele.v3i2.8081
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Inferencing in Listening: Depth of Vocabulary Knowledge and Listening Proficiency

Abstract: Lexical inferencing as an efficient strategy to deal with unfamiliar words is suggested to be the most commonly used strategy among students, thus it has attracted much attention in the comprehension literature. While literature abounds with inferencing studies in reading, few studies have delved into the processes involved in listening. This study sought to investigate the role of depth of vocabulary knowledge (DVK) in lexical inferencing success and determine the relationship between students' DVK and listen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…In this variable, all of the indicators acquired a level description of "moderate" except for the creative level with low descriptive level.These results align with the findings of Raju and Madhuri (2022), who similarly discovered a high level of learning style preference among secondary school students in their study. The result also resonates withFoomani's (2015) study, which also identified a high level of lexical inferencing strategies among proficient college listeners. Also, this outcome echoes Yusoff et al's (2016) findings, which similarly indicated a moderate level of reading comprehension among students, highlighting the necessity for effective guidance in text comprehension.…”
supporting
confidence: 84%
“…In this variable, all of the indicators acquired a level description of "moderate" except for the creative level with low descriptive level.These results align with the findings of Raju and Madhuri (2022), who similarly discovered a high level of learning style preference among secondary school students in their study. The result also resonates withFoomani's (2015) study, which also identified a high level of lexical inferencing strategies among proficient college listeners. Also, this outcome echoes Yusoff et al's (2016) findings, which similarly indicated a moderate level of reading comprehension among students, highlighting the necessity for effective guidance in text comprehension.…”
supporting
confidence: 84%